GRAMMATICAL ACCURACY IN BUSINESS ENGLISH PRESENTATIONS: AN ERROR ANALYSIS OF UNDERGRADUATE MANAGEMENT STUDENTS - Ade Kristianus Kaloeti; Sri Ani Puji Setiawati (Wiralodra English Journal, 2026)
Grammatical accuracy plays a crucial role in the effectiveness of Business English presentations, particularly for management students who are expected to communicate professionally in academic and workplace contexts. This study aims to identify and analyze grammatical errors produced by undergraduate management students during Business English presentations. Employing a quantitative research design, the study involved 20 seventh-semester management students: 10 from Immanuel Christian University and 10 from Muhammadiyah University of Yogyakarta. The data were collected through recorded Business English presentations and analyzed using Corder’s Error Analysis model, which consists of error identification, classification, explanation, and evaluation. The findings reveal that students frequently committed errors in verb tense, subject–verb agreement, articles, prepositions, and sentence structure. Verb tense errors emerged as the most dominant category, followed by subject–verb agreement and article misuse. The results indicate that despite having advanced academic standing, students still encounter significant grammatical challenges in oral academic communication. This study highlights the need for more focused grammar instruction integrated with speaking practice in Business English courses. The findings are expected to contribute to pedagogical improvements in English for Specific Purposes (ESP), particularly Business English instruction at the undergraduate level.